Karakteristik Model Pendidikan Islam Nusantara: Kajian Filosofis dan Kontribusinya Terhadap Pendidikan Era Modern - Achsan Isroi; Nur Cholid; Ghufron Hamzah (Journal of Innovative and Creativity, 2026)
Islamic Nusantara Education is an educational system rooted in universal Islamic values and local wisdom. This article examines the characteristics of Islamic Nusantara education from a philosophical perspective, including educators, students, materials, educational tools, and the environment. The study employed a qualitative-descriptive approach based on literature. The results indicate that this educational model is capable of addressing contemporary educational challenges with an approach incorporating moderation, spirituality, and local culture. This article also offers contributions and suggestions for strengthening character education based on Islamic Nusantara values in the era of globalization.